(untitled) (Bangladesh Journal of Agricultural Research, 2022)
Thirty-six genotypes of chilli (Capsicum spp.) from diverse sources were evaluated at the Regional Spices Research Station, BARI, Gazipur during February 2017 to November 2018 to select the promising genotype(s) for breeding. Distinct variation among the genotypes was observed in all the qualitative parameters except seed colour and fruiting behavior. The genotype CO 525 and CO 634 took minimum days for 1st flowering (50 days) and first fruit set (59 days), while the genotype CO 633 took the maximum for 1st flowering and first fruit set (125 and 141 days). Plant height ranged from 46 cm (CO 610) to 119cm (CO613). Single fruit weight ranged from 0.72 g (CO629) to 7.81g (CO642), while fruit length ranged from 2.90cm (CO645) to 12.68 cm (CO631). Pedicel length was maximum in CO643 (5.52 cm) and minimum in CO639 (1.50 cm). The genotype CO 611-2 had the maximum number of fruits/plant (342) whereas the genotype CO640 had the minimum no. of fruits/plant (41.33). The genotype CO631 produced the maximum weight of fruits/plant (628.33g). The maximum number of fresh seeds was obtained from CO635 (93.20/fruit) and it was the lowest in C0645 (18). The highest weight of fresh seeds/fruit was obtained from CO525 (0.61 g) and the lowest from CO 639 (0.13 g). The maximum fruit yield was recorded from CO 631 (23.88 t/ha) closely followed by CO635 (19.21 t/ha) and CO 637 (19.12 t/ha). Results revealed that the genotypes differed significantly in most of the parameters and offer a good scope for selection of better genotypes as parents for the desired traits. Bangladesh J. Agril. Res. 45(3): 335-348, September 2020